The Borda count with weak preferences - Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2021)
I consider an extension of the Borda count to the case when individuals can have weak preferences, and I show that it satisfies several normatively appealing axioms. The first axiom is an extension to the case of weak preferences of the Modified Independence of Irrelevant Alternatives axiom inMaskin (2020a). The second axiom is a new axiom which I call Up-Down Symmetry. The remaining axioms are more standard.
Keywords: D71; 330; Social choice; Borda rule